1994
DOI: 10.1152/ajpregu.1994.267.4.r916
|View full text |Cite
|
Sign up to set email alerts
|

Perinuclear zone and diagonal band lesions enhance angiotensin responses of rat supraoptic neurons

Abstract: Sinoaortic denervation in the rat is associated with an increased sensitivity of vasopressin neurons in the supraoptic nucleus (SON) to peripheral angiotensin II (ANG II). Lesion studies have indicated that the diagonal band of Broca (DBB) and the perinuclear zone of the SON in the lateral hypothalamus (PNZ) are essential components in the central pathway for the baroreceptor inhibition of vasopressin SON neurons. The present study examined the effect of ibotenate lesions in either the DBB or the lateral hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 0 publications
6
35
0
Order By: Relevance
“…When a peripheral vasoconstrictor is delivered intravenously to increase blood pressure, vasopressinergic magnocellular neurones are inhibited. Ibotenic acid lesions, similar to those produced in this study, result in a decrease in the number of neurones inhibited by blood pressure increases (16, 23). In addition, in DBBX rats, the response of vasopressin‐secreting neurones to i.v.…”
Section: Discussionsupporting
confidence: 67%
“…When a peripheral vasoconstrictor is delivered intravenously to increase blood pressure, vasopressinergic magnocellular neurones are inhibited. Ibotenic acid lesions, similar to those produced in this study, result in a decrease in the number of neurones inhibited by blood pressure increases (16, 23). In addition, in DBBX rats, the response of vasopressin‐secreting neurones to i.v.…”
Section: Discussionsupporting
confidence: 67%
“…Further, sham water deglutition stimulates diuresis in anesthetized rats, and this effect is blocked by bilateral sectioning of the superior laryngeal nerve (58). Lastly, the NTS communicates extensively with a network of nuclei participating in cardiovascular regulation of vasopressin release that includes the diagonal band of broca (14,23), locus ceruleus (LC) (24), and parabrachial nucleus (PBN) (22). Therefore, these regions could participate in an alternative pathway involved in preabsorptive regulation of AVP and will be examined in our future endeavors.…”
Section: Effect Of Rehydration or Sham Rehydration On C-fos And Avpmentioning
confidence: 99%
“…The PNZ contains inhibitory interneurons (28,33,67) that reduce activity of phasic AVP neurons in the SON (4,14,25). We have previously demonstrated that c-Fos staining is increased in the PNZ following water but not saline rehydration (22).…”
Section: Effect Of Rehydration or Sham Rehydration On C-fos And Avpmentioning
confidence: 99%
“…In addition, another receptor with a high affinity for NPFF, namely, NPFF2 (FF2; Bonini et al, 2000;Elshourbagy et al, 2000), also is not expressed in the human SO . However, high numbers of NPFF fibers in the PNZ might be involved in indirect regulation of SO neurons, in that studies in the rat have shown that an interneuronal network located in the PNZ affects the activity of neurosecretory neurons within the SO (Jhamandas et al, 1991;Cunningham et al, 1994;Herbison, 1994).…”
Section: Distribution Of Npff In the Human Forebrainmentioning
confidence: 99%